Virtual Power Plant for Smart Grid Ready Buildings and Customers - Rotger-Griful, Sergi; Jacobsen, Rune Hylsberg (Technical Report Electronics and Computer Engineering, 2016)
This report contains a summary of results from the ForskEL project: Virtual Power Plant for Smart Grid Ready Buildings and Customers.